Strategi Manajemen Kesehatan di Rumah Sakit: Memaksimalkan Pelayanan Pasien dan Efisiensi Operasional - Bambang Sulistyo; Dety Mulyanti (Universitas Muhamadiyah Manado, 2023)
Based on the Regulation of the Minister of Health of the Republic of Indonesia No. 72 of 2016, a hospital is an individual health service facility that provides inpatient and outpatient care, therefore quality services that must be fulfilled by hospitals. In order to maximize the service to the patient, the operational system must be made more efficient and efficient. The study uses a review literature study approach using several sources selected based on the inclusion and exclusion criteria that the researchers have established that an efficient operating system can provide optimal service to the patient. This will give a positive response to patient satisfaction.